2007
DOI: 10.1016/j.expneurol.2007.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment with paroxetine ameliorates behavioral deficits and retards the development of amyloid and tau pathologies in 3xTgAD mice

Abstract: A history of depression is a risk factor for Alzheimer's disease (AD), suggesting the possibility that antidepressants administered prophylactically might retard the disease process and preserve cognitive function. Here we report that pre-symptomatic treatment with the antidepressant paroxetine attenuates the disease process and improves cognitive performance in the 3xTgAD mouse model of AD. Five month-old male and female 3xTgAD and non-transgenic mice were administered either paroxetine or saline daily for 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 104 publications
11
133
1
Order By: Relevance
“…The open field and elevated plus maze test confirmed that anxietylike behaviors continue to exist in the late stages of this mouse AD model, similar to the Tg2576 (Gil-Bea et al 2007;Lassalle et al 2008), J20 (Harris et al 2010;Cissé et al 2011), and 5xFAD mice (Wirths et al 2010;Shukla et al 2013), all of which also exhibit anxietyrelated behavior deficits in the elevated plus maze task. However, there is no anxiety-related behavior abnormality in the APP/PS1 double knock-in mice from 7 to 24 months old (Webster et al 2013); while 3xFAD mice show decreased anxiety-related behavior in the open field and elevated plus maze test (Nelson et al 2007;Filali et al 2012). The variability of anxiety-related behavior in these commonly used AD mouse models supports a heterogeneous range of noncognitive symptoms caused by Aβ-related pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…The open field and elevated plus maze test confirmed that anxietylike behaviors continue to exist in the late stages of this mouse AD model, similar to the Tg2576 (Gil-Bea et al 2007;Lassalle et al 2008), J20 (Harris et al 2010;Cissé et al 2011), and 5xFAD mice (Wirths et al 2010;Shukla et al 2013), all of which also exhibit anxietyrelated behavior deficits in the elevated plus maze task. However, there is no anxiety-related behavior abnormality in the APP/PS1 double knock-in mice from 7 to 24 months old (Webster et al 2013); while 3xFAD mice show decreased anxiety-related behavior in the open field and elevated plus maze test (Nelson et al 2007;Filali et al 2012). The variability of anxiety-related behavior in these commonly used AD mouse models supports a heterogeneous range of noncognitive symptoms caused by Aβ-related pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to symptomatic benefits, much preclinical evidence suggest disease-modifying effects of select SSRIs, such as activities involving Aβ reduction and increased hippocampal neurogenesis [74]. Stimulation of 5-hydroxytryptamine receptors was shown to promote nonamyloidogenic processing of APP [76][77][78][79], and the SSRIs paroxetine and imipramine reduced Aβ levels in mouse models of AD [80]. Direct analysis of brain interstitial fluid using microdialysis revealed that citalopram, desvenlafaxine, and fluoxetine reduced the interstitial fluid Aβ levels in presenilin 1 APP double transgenic mice [81].…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Several studies have also assessed the effect of serotonin receptors (5HT-Rs) on APP processing and Aβ levels. Activation of select 5HT-Rs increases nonamyloidogenic processing of APP in vitro (14)(15)(16) and chronic administration of selective serotonin reuptake inhibitors (SSRIs) reduces brain Aβ levels in mice (17)(18)(19).…”
mentioning
confidence: 99%